Catalysis of nickel nanodomains on Li-F dissociation for high-capacity fluoride cathodes with prior delithiation ability. (1st December 2022) - Wu, Tao; Cui, Yanhua; Wei, Kaiyuan; Lai, Chuanzhong; Zhao, Yu; Ni, Shuang; Chen, Yongjin; Gao, Xiang; Cui, Yixiu; Li, Chilin
Abstract: Transition metal fluoride is being considered as one of the most promising cathode materials due to its feasibility of high-voltage conversion reaction and high theoretical capacity. But the low solubility of LiF in fluoride is prone to degrade the electrode conductivity and Li-resource supply from fluoride cathode side, therefore limiting the reversibility of conversion reaction and its practical use in Li-ion batteries. Here, we propose a catalysis effect of Ni nanodomains to activate the Li-F splitting with much lower dissociation energy and to enable the LiF/Fe/Ni ternary cathode with superior conversion reaction capacity (600 mAh g −1 ) and rate performance (306 mAh g −1 at 3.8 A g −1 ). The crowded effect between LiF and dual-metal phases suppresses the growth of crystal grains and promotes the enrichment and penetration of LiF-Fe-Ni triple-phase interfaces. This compact interface contact endows the lithiated fluoride with an ultrahigh initial charge capacity exceeding 600 mAh g −1 and lowered charge plateau below 3.5 V. The preservation of interconnectivity and catalytic activity of electron conductive network enables the high reversibility of LiF splitting/recombination under high energy efficiency of 76%, as well as the electrochemical synthesis of rutile-like Nix Fe1−x F2 solid-solution phase. This fluoride cathode enables a release of high energy density (1414 Wh kg −1 ) under a power density of 849 W kg −1 and the energy density can still be preserved at 629 Wh kg −1 under an extremely high power densities of 3374 W kg −1 . This work paves the way to develop the high-energy-density fluoride cathodes with the prior delithiation ability, which can lessen and even eliminate the use of Li metal at anode side. Graphical Abstract: ga1 Highlights: A catalysis of Ni nanodomains on activating Li-F splitting enables LiF/Fe/Ni cathode with superior conversion capacity. The compact interface contact endows the lithiated fluoride with a high initial charge capacity and lowered charge plateau. The preservation of catalytic activity of electron conductive network enables the high reversibility of LiF splitting. This fluoride cathode enables the high energy density of 1414 Wh kg-1 under the power density of 849 W kg-1. This work paves the way to develop high-energy-density fluoride cathodes with the prior delithiation ability.